SUMOylation of OsPSTOL1 is essential for regulating phosphate starvation responses in rice and Arabidopsis - Mukkawar, Vaishnavi; Roy, Dipan; Sue-ob, Kawinnat; Jones, Andrew; Zhang, Cunjin; Kumar Bhagat, Prakash; Kakkunnath, Sumesh M.; Heuer, Sigrid; Sadanandom, Ari (Frontiers in Plant Science, 2024)
Although rice is one of the main source of calories for most of the world, nearly 60% of rice is grown in soils which is low in phosphorus especially in Asia and Africa. Given the limitations of bioavailable inorganic Phosphate (Pi) in soils, it is important to develop crops tolerant to low phosphate in order to to boost food security. Due to the immobile nature of Pi, plants have developed complex molecular signalling pathways that allows them to discern changes of Pi concentrations in the environment and adapt their growth and development. Recently, in rice it was shown that a specific serine-threonine kinase known as Phosphorusstarvation tolerance 1 (PSTOL1) is important for conferring low phosphate tolerance in rice. Nonetheless, knowledge about the mechanism underpinning PSTOL1 activity in conferring low Pi tolerance is very limited in rice. Post Translation Modifications (PTMs) play an important role in plants in providing a conduit to detect changes in the environment and influence molecular signalling pathways to adapt growth and development. In recent years the PTM SUMOylation has been shown to be critical for plant growth and development. It is known that plants experience hyperSUMOylation of target proteins during phosphate starvation. Here we demonstrate that PSTOL1 is SUMOylated in planta, and this affects its phosphorylation activity. Further, we also provide new evidence for the role of SUMOylation in regulating PSTOL1 activity in plant responses to Pi starvation in rice and Arabidopsis. Our data indicated that overexpression of the non -SUMOylatable version of OsPSTOL1 negatively impacts total root length and total root surface area of rice grown under low Pi. Interestingly, our data also showed that overexpression of OsPSTOL1 in a non-cereal species, Arabidopsis also positively impacts overall plant growth under low Pi by modulating root development. Taken together our data provide new evidence for the role of PSTOL1 SUMOylation in mediating enhanced root development for tolerating phosphate limiting conditions.